(untitled) (Al-Academy, 2023)
When the television set appeared on the scene for the first time in the forties and fifties of the twentieth century, it caused a major change in the world in various fields, the most important of which was the industrial field. Due to the great demand from viewers to follow this amazing device, industrialists It was followed by the video equipment industry in the 1980s; Then HDTV in the late 1990s. The twenty-first century brought about the emergence of television, tablets, and computers of all kinds. Then mobile phones, and the story of the emergence of television begins in 1926 AD, specifically on the twenty-seventh of January When scientists and researchers gathered in a hall at the Royal Institute in London in front of a screen, they looked at it with longing and anxiety, waiting for something mysterious and exciting. Soon, some flashes appeared on its surface, which began to take on their features and lines, turning into moving illusions, but they were not clear enough. At that moment, those gathered jumped up, cheering and congratulating each other. They were witnesses to a turning point in history in media, journalistic and artistic work, as they witnessed the first successful experiment with history’s greatest technological inventions in the fields of communications and media. Since that time, the role of that screen, which was later called television, in the lives of the masses has increased, and it has truly become a miracle of the twentieth century due to its reliance on sound, image, and movement